UNUSUAL PULMONARY PRESENTATION OF WILMS TUMOR MESTASTASIS DETECTED BY ABDOMINAL ULTRASOUND WITH REVIEW OF THE LITERATURE (Journal of Biomedical Investigation, 2010)
We report a case of 9 years old boy that presented at 5 years with nephroblastoma. He had an unusual metastatic deposit at the right lung base after 3 years following surgery and courses of cytotoxics. Metastasis to the lungs following Nephroblastoma is common' but the presentation as an elevation of the right hemidiaphragm on a chest radiograph and a right basal mass are rare. The objective of the report is to highlight the fact that elevation of the diaphragm in patients with nephroblastoma may well be hiding a metastatic deposit.
Keywords: Wilms tumor; Metastasis; Ultrasonography